2000
DOI: 10.1006/jmaa.2000.6882
|View full text |Cite
|
Sign up to set email alerts
|

Moments and Positivity

Abstract: We express the structure of some positive polynomials in several variables, as squares of rational function with universal denominators, using functional analysis methods. ᮊ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Note that similar results in the scalar case have been obtained in ( [3], Theorem 3.5), as well as ( [11], Corollary 4.3).…”
Section: Vol 49 (2004)supporting
confidence: 66%
See 1 more Smart Citation
“…Note that similar results in the scalar case have been obtained in ( [3], Theorem 3.5), as well as ( [11], Corollary 4.3).…”
Section: Vol 49 (2004)supporting
confidence: 66%
“…Factorization using fixed denominators has been of more recent interest. The reader is referred, for example, to [12], [11] and [3]. The latter, in particular, considers factorizations where the denominators have the same form as those here.…”
Section: Vol 49 (2004)mentioning
confidence: 99%
“…A sequence {γ ij } 0≤i+j≤m satisfying (1.1) will be called a truncated moment sequence and the solution µ is said to be a representing measure associated to the sequence {γ ij } 0≤i+j≤m . In [34] J. Stochel has shown that solving TCMP solves the widely studied Full Moment Problem (see, for example, [1,2,3,17,29,30,33,36]). More precisely, a full moment sequence {γ ij } i,j∈Z+ admits a representing measure if and only if each of its truncation γ (m) admits a representing measure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its importance for applications, a complete solution of TMP would readily lead to a solution of the full moment problem, via a weak-* convergence argument, as shown by J. Stochel [40]. While we primarily focus on truncated moment problems, the full moment problem (in one or several variables) has been widely studied; see, for example, [1], [2], [17], [23], [24], [25], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [41], [42], [43].…”
Section: Introductionmentioning
confidence: 99%